Characteristics of Canadian youth-perpetrated homicides - Woodworth, Michael (Criminal justice and behavior, 2013)
Youth-perpetrated homicide has considerable impact on our society and justice system. Unfortunately, youth-perpetrated homicide is an understudied crime and even less research has been conducted specific to a Canadian population. Two decades ago, Meloff and Silverman published the most thorough examination of youth-perpetrated homicide in Canada. Since that time, it has been proposed that the motivations and characteristics of youth violence have changed in a number of important ways. The present study expands on previous limited empirical studies and investigation into features of youth homicides using a sample of 105 Canadian youth homicide offenders. A number of important differences were observed. For instance, there were substantially more multiple-perpetrator, stranger, and instrumental homicides. Results are considered in relation to trends observed in Canada and the United States.